A CD22-Shp1 phosphatase axis controls integrin beta(7) display and B cell function in mucosal immunity - Ballet, Romain; Brennan, Martin; Brandl, Carolin; Feng, Ningguo; Berri, Jeremy; Cheng, Julian; Ocon, Borja; Alborzian Deh Sheikh, Amin; Marki, Alex; Bi, Yuhan; Abram, Clare L.; Lowell, Clifford A.; et al. (Nature Immunology, 2021)
Lymphocyte homing to the gut and Peyer's patches requires expression of integrin alpha(4)beta(7). Ballet and colleagues report that B cell expression of CD22 is required to specifically retain surface expression of beta(7) integrin molecules, thereby promoting B cell retention in the gut and optimal gut mucosal antibody responses.
CRIS-Team WoS Importer:2021-03-05